LOOKING AT OBJECTIVE AND SUBJECTIVE HEALTH IN CENTENARIANS: ALWAYS IN AGREEMENT?. (11th November 2018) - Araujo, L; Teixeira, L; Ribeiro, O; Paul, C
Abstract: Centenarians′ objective health is often characterized by functional and health problems associated with their long-life and age-related problems. Nevertheless, their self-rated health (SRH) may not be necessarily negative. There is a large body of literature concerning SRH in later life but lack of evidence about one's perception of health and its associated factors in very advanced ages. This study aims to analyse the relationship between subjective and objective health status in a sample of centenarians (n=127; Mage = 101.1 years, SD 1.5). Subjective health was assessed by a SRH single-item, and objective health by considering the number of reported diseases and a functional capacity scale. Main health characteristics are described as well as examined the association between objective and subjective health indicators and other relevant variables (e.g., individual resources). Results revealed that almost half of the sample has a positive (good, very good or excellent) health appraisal. Many of these individuals have 3 or more diseases and are dependent in their ADL. Objective and subjective measures of health are discordant is some cases. Results revealed that centenarians′ SRH could be determined by other factors than the objective health ones. Having diseases and functional dependence at 100 years old may not mean to have a bad SRH. The high variability in SRH and the discordance between objective and subjective measures are a proof of centenarians ′capacity of adaptation and the existence of psychosocial resources that may be decisive for the perception and handling of health status at such an advanced age.